2 - Illicit Financial Flows in Southern Africa: Exploring Implications for Socio-economic Development - Gumede, Vusi; Fadiran, David (Africa Development, 2019)
This article views Illicit Financial Flows (IFFs) as any illegal and corrupt practice to acquire money without the due process that is in line with international financial and trade regulatory frameworks. Based on this working definition, the article explores IFFs in the mining sectors in four countries (the Republics of Botswana, Namibia, South Africa and Zimbabwe) with a specific focus on the socio-economic implications for communities in the mining or former mining areas. Measurement issues are also attempted. Indeed, IFFs have severe implications for the communities (as for countries). Although the results are mixed, regarding the quantification of IFFs in the mining sector, it is clear that IFFs have major negative effects on welfare and political stability. Estimates show high levels of IFFs through trade mis-invoicing for the mining sector in all the four countries.